Hot Pressing of Boron Carbide Based Ceramic Composites - Svec, Pavol; Gabrisova, Zuzana; Brusilova, Alena (Manufacturing Technology Journal, 2020)
Ceramic composite materials based on boron carbide were hot pressed utilising in situ reaction of boron carbide powder with 40 wt.% of titanium dioxide sintering additive. The samples were prepared at sintering temperature of 1850 °C, pressure of 35 MPa, and time of 60 min in vacuum atmosphere of about 20 Pa. Optimisation of sintering regime concentrating on both heating stage of sintering and application of pressure enabled to prepare fully dense ceramic composite materials composed of boron carbide matrix with 29.5 vol.% of titanium diboride secondary phase. The ceramic composite reached average density of 99.3 %, hardness of 29.8 GPa, and fracture toughness of 6.9 MPa.m1/2.
Keywords: boron carbide; ceramic composite; sintering; microstructure